2014
DOI: 10.15623/ijret.2014.0323047
|View full text |Cite
|
Sign up to set email alerts
|

Parametric Optimisation of Pulsed – Tig Welding Process in Butt Joining of 304l Austenitic Stainless Steel Sheets

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 15 publications
(4 reference statements)
0
1
0
2
Order By: Relevance
“…Ne kep eğme testleri sırasında ne de kök eğme testleri sırasında herhangi bir çatlama ya da kırılma gözlenmemiştir. Kumar ve diğerleri, TIG kaynağı ile AISI 304 paslanmaz çeliğini birleştirdikleri ve birleştirmelere üç nokta eğme testi uyguladıkları çalışmada herhangi bir açılma ya da çatlak oluşumuna rastlanmadığını rapor etmişlerdir [38]. Kar ve diğ.…”
Section: Eğme Deneyi Sonuçlarıunclassified
“…Ne kep eğme testleri sırasında ne de kök eğme testleri sırasında herhangi bir çatlama ya da kırılma gözlenmemiştir. Kumar ve diğerleri, TIG kaynağı ile AISI 304 paslanmaz çeliğini birleştirdikleri ve birleştirmelere üç nokta eğme testi uyguladıkları çalışmada herhangi bir açılma ya da çatlak oluşumuna rastlanmadığını rapor etmişlerdir [38]. Kar ve diğ.…”
Section: Eğme Deneyi Sonuçlarıunclassified
“…Так же известно, что моноксид углерода, нагретый выше определенной температуры, вступает в активные химические реакции с кислородом воздуха, окисляясь до углекислого газа [5]. Поэтому с целью нейтрализации вредного действия монооксида углерода было предложено нагревать подогреваемый для защиты сварочной дуги газ выше температуры воспламенения [6].…”
Section: использование восстановительной атмосферы для сварки сталей аустенитного классаunclassified
“…They found that there were large thermal stresses arising in these joints during temperature fluctuations owing to the difference in thermal expansion coefficients. Dinesh Kumar et al [13] investigated the effect of different parameters including current, voltage, stand-off distance, weld speed and gas flow to improve welding quality. They found that weld speed and input current were the most significant parameters.…”
Section: Introductionmentioning
confidence: 99%